New “schizophrenias” for the Schizohistory: history divulgation in mass and digital media, and its impact in classrooms (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
This work aims to reflect on the importance of the so-called ‘historical divulgation’ or ‘mass history’ for the discussion of the specific didactics of history. Epistemological and historiographic features of this phenomenon are delineated and bridges are drawn between it and the problems of history teaching considered relevant by specialized bibliography. Emphasis is placed on the questions and problems offered by web 2.0 as a collaborative digital environment paradigm and the historical cultural products that circulate through it, and the way in which they are consumed by students and history teachers. To this end, the role of historical best-sellers and Wikipedia is briefly analyzed. In this sense, it is understood that the role of the public communication of History appears as a product of wide resonance that would have performative effects in the way how History is taught in classrooms within the framework of the digital environment of XXI century.
Keywords: History divulgation; best-sellers; Wikipedia; history teaching